Effect of workshop training along with simulation and support of labor practitioners on their attitude and performance in conducting routine episiotomy - Mitra Eftekhari Yazdi; Mostafa Rad; Marzie Torkmannejad Sabzevari (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Routine episiotomy is a common procedure to shorten the second stage of labor. The attitude of individuals is an important factor in episiotomy, which is often carried out without an indication. Therefore, this study aimed to determine the effect of education and support of labor practitioners on their attitude and performance in conducting routine episiotomy. MATERIALS AND METHODS: This was a quasi-experimental study. A sample of 66 midwives, physicians, and midwifery faculty members were selected through the convenience sampling method. The data collection instrument was the questionnaire of personnel's attitude toward episiotomy. This questionnaire was completed by the participants before and 3 months after the intervention. A 16-h workshop about the education of natural childbirth for 2 days was performed on the experimental group. Data analysis was performed using paired t-test and Pearson's correlation test. RESULTS: The findings showed that mean attitude of the participants toward episiotomy was 50.5 ± 1.58 before the intervention, which changed to 61.18 ± 2.5 after the intervention, demonstrating a significant difference between the attitude of the participants before and after the intervention using paired t-test (P < 0.001). In terms of the performance of the midwives, participating in the research, there was a significant decrease in the number of deliveries without episiotomy. CONCLUSIONS: According to the results of the study, education and support of midwifery personnel can change the attitude and performance of these individuals in conducting a routine episiotomy, thereby reducing the number of child deliveries without episiotomy.